Hypoplastic Left Heart Syndrome – Unresolved Issues - Arnold, Raoul Roman; Loukanov, Tsvetomir; Gorenflo, Matthias (Frontiers in Pediatrics, 2014)
Hypoplastic left heart syndrome (HLHS) is one of the most challenging congenital heart defects. At present it is expected that - at best - 70% of newborns with HLHA will reach adulthood. This review addresses the problems of right ventricular failure and insufficient growth of pulmonary vasculature in these patients. In order to further improve long-term prognosis translational research to control right ventricular function and growth of pulmonary arteries and progress in chronic circulatory support are clearly needed to provide a further improvement for adults with HLHS.